Determinan Keputusan Menggunakan Jasa Perbankan Syariah - Bunga Alisa; Galya Adisti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The development of the number of customers at Islamic banks certainly shows the public's interest in deciding whether to remain customers or not. Residents of Comal District, which is dominated by Islam, should choose to use Islamic banks. Of course, the interest of the people of Comal District in becoming part of an Islamic bank is influenced by many factors, including religiosity, emotional motivation, and rational motivation. This type of research is field research with a quantitative research approach. The population in this study were residents of the Comal sub-district with a sample of 96 respondents. The source of data used is primary data. Data analysis in this study used the validity test, reliability test, normality test, test multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test (R2)), T-test, and F test through IBM SPSS 26 program. The study's results show that religiosity, emotional motivation, and rational motivation significantly affect the decision-making of residents of the Comal sub-district to use Islamic banking services. Simultaneously, religiosity also influences the decision to use Islamic banking services.